2017
DOI: 10.1111/aos.13404
|View full text |Cite
|
Sign up to set email alerts
|

Early microvascular retinal changes in optical coherence tomography angiography in patients with type 1 diabetes mellitus

Abstract: M1 patients with no or mild signs of retinopathy have reduced parafoveal vessel density in the DCP on OCTA when compared to non-diabetic controls. These OCTA findings suggest that parafoveal capillary nonperfusion is an early process in DM1-related retinal changes and occurs initially at the level of the DCP. Further investigation is needed to understand the prognostic role of these vascular changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
134
2
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(166 citation statements)
references
References 42 publications
20
134
2
10
Order By: Relevance
“…Several studies also suggest that OCTA parameter alterations in the deep vascular layer are affected more severely than in the superficial vascular layer in NPDR [10, 11, 14-16, 17, 21, 23, 26]. OCTA parameters at the deep vascular layer were most significantly affected in patients with DME [4, 29-32].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies also suggest that OCTA parameter alterations in the deep vascular layer are affected more severely than in the superficial vascular layer in NPDR [10, 11, 14-16, 17, 21, 23, 26]. OCTA parameters at the deep vascular layer were most significantly affected in patients with DME [4, 29-32].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Increased FAZ area was present in both superficial and deep vascular layers of patients with NPDR [8, 14, 17-20]. In patients with type 1 diabetes and mild NPDR, vessel density was significantly reduced only in the deep vascular layer compared to control subjects [21]. In mild NPDR, a reduction of the vessel density at the deep vascular layer occurred in earlier stages (mild NPDR) than in the superficial vascular layer [17].…”
Section: Octa Parameters In the Superficial Deep And/or Intermediatmentioning
confidence: 99%
See 1 more Smart Citation
“…42 The initial lesions along with endothelial proliferation, pericyte damage, and microaneurysms have been identified to be focal and in the posterior pole 59 and are therefore more likely to align with our study results. In addition, a decrease in the density of deep capillary plexus at the macular area has been noted in patients with no or a mild stage of DR. 60 Changes in the capillary plexus and therefore the blood supply and nutrients may affect the normal integrity and/or functioning of the ganglion cells and other neural cells in the retina; these are associated with diabetes-induced accelerated ganglion cell death and likely involve bipolar cells and also photoreceptors. 42 Therefore, the number of fields photographed is less likely to affect our study results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is evidence that capillary rarefaction starts in the deep capillary plexus [20,25]. Moreover, Agemy et al [24] reported that the loss of capillary density was greater in the superficial capillary plexus than in the deep capillary plexus.…”
Section: Discussionmentioning
confidence: 99%